Post office at Lourdes - Meaney, Carmelita (1976)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « History of the community of Lourdes and the people that live there ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "History of the community of Lourdes and the people that live there"